DETERMINANTS OF GREEN LIFESTYLE FACTORS TO MAINTAIN THE SUSTAINABILITY OF ENVIRONMENTAL TOURISM BUSINESS - Farida, Dessy Noor; Adhitya, Fajar; Rahmawari, Fefi (KEUNIS, 2024)
Based on interviews with tourism object managers, it was found that generation z tourists often take disgraceful actions by displaying behavior that pollutes and even damages tourist attractions. This study examines how much influence (tourist attitudes, subjective norms, expected behavioral control on tourist intentions), then examines the effect of tourist intentions on environmentally responsible tourism behavior and examines its effect on green lifestyles. This research is a type of quantitative research and primary data source. The population of this study is Generation Z tourists who have visited in the last three years. The samples obtained were 224 respondents. The data analysis technique in this study uses the Warp PLS (Partial Least Square) structural equation model. The results show that all hypotheses are accepted. Attitude, Subjective Norm, and Behavioral control that is felt to affect intentions. The higher the tourists' intention to be responsible for the environment, the better the behavior responsible for the environment. The results show that the better the behavior to be responsible for the environment, the higher the green lifestyle. With this research, it is hoped that it can raise awareness for the younger generation to be more concerned about environmental sustainability around tourism sites and participate in preserving the environment